Effect of high-dose polymeric nanoparticle micellar paclitaxel on improved progression-free survival in patients with optimally resected stage III or IV high-grade carcinoma of the ovary: a prospective cohort study with historical controls - Park, Soo Jin; Son, Joo-Hyuk; Kong, Tae-Wook; Chang, Suk-Joon; Kim, Hee Seung (Frontiers in Oncology, 2024)
We evaluated the effect of high-dose polymeric nanoparticle micellar paclitaxel (PM-Pac) on survival in patients with stage III-IV high-grade serous ovarian cancer (HGSC) who underwent upfront surgery.Methods. We prospectively recruited the patients who received PM-Pac (280 mg/m 2 ) and carboplatin at an area under the curve (AUC) of 5 (cohort 1) in two tertiary centers between October 2015 and June 2019. As historical controls, we retrospectively collected data on those who received paclitaxel (175 mg/m 2 ) and carboplatin (AUC 5; cohort 2) or paclitaxel (175 mg/m 2 ), carboplatin (AUC 5) and bevacizumab (15 mg/kg; cohort 3).Results. A total of 128 patients were divided into cohorts 1 (n=49, 38.3%), 2 (n=53, 41.4%), and 3 (n=26, 20.3%). Cohort 1 showed better progression-free survival (PFS) than cohort 2 in all patients and those treated with optimal debulking surgery (ODS; median, 35.5 vs. 28.1 and 35.5 vs. 28.9 months; p≤0.01) despite no difference in PFS between cohorts 1 and 3 and between cohorts 2 and 3. In particular, stage III disease was a favorable factor for PFS, whereas cohort 2 was related to worse PFS (adjusted hazard ratios, 0.456 and 1.834; 95% confidence interval, 0.263 -0.790 and 1.061 -3.171), showing no difference in PFS between cohorts 1 and 3 in those treated with ODS.Conclusions. High-dose PM-Pac improved PFS compared to conventional chemotherapy, and the change of paclitaxel to PM-Pac had as much effect on PFS as the addition of bevacizumab in patients with stage III-IV HGSC who underwent ODS.